Transcriptome signature changes in the liver of a migratory passerine - Frias Soler, Roberto Carlos; Kelsey, Natalie A.; Villarín Pildaín, Lilian; Wink, Michael; Bairlein, Franz (Genomics, 2022)
The liver plays a principal role in avian migration. Here, we characterised the liver transcriptome of a long-distance migrant, the Northern Wheatear (Oenanthe oenanthe), sampled at different migratory stages, looking for molecular processes linked with adaptations to migration. The analysis of the differentially expressed genes suggested changes in the periods of the circadian rhythm, variation in the proportion of cells in G1/S cell-cycle stages and the putative polyploidization of this cell population. This may explain the dramatic increment in the liver’s metabolic capacities towards migration. Additionally, genes involved in anti-oxidative stress, detoxification and innate immune responses, lipid metabolism, inflammation and angiogenesis were regulated. Lipophagy and lipid catabolism were active at all migratory stages and increased towards the fattening and fat periods, explaining the relevance of lipolysis in controlling steatosis and maintaining liver health. Our study clears the way for future functional studies regarding long-distance avian migration.
Gesehen am 14.05.2022